The Influence of Socioeconomic Factors on Early Marriage - Novi Yarsah, Waldi; Tanzil, Dolly; Bahrul Ulum, Muhammad; Syaifullah, Ahmad (Jurnal Ilmiah Ekonomi Global Masa Kini, 2025)
The core problem of this research focuses on analyzing the influence of socioeconomic factors on the high of early marriage in Empat Lawang Regency. This study specifically aims to test and analyze the causal relationship between key socioeconomic factors, which include respondent’s education level, mother’s education level, father’s education level, parents’ employment status, and household income, on the probability of early marriage occurrence. The primary focus is to identify the strongest predictor variable. This research employs a quantitative approach using descriptive and verification methods, chosen for their effectiveness in statistically measuring and testing hypotheses. The main data were processed through multiple logistic regression analysis. This technique is highly appropriate considering the dependent variable (early marriage) is dichotomous. The sample used consisted of 160 married female respondents, divided into 80 women married under the age of 19 and 80 women married over the age of 20. The empirical analysis results show that several factors statistically influence the probability of early marriage, including the respondent’s education level, father’s education level, and household income. Nevertheless, the test results indicate that the respondent’s education level is the factor with the strongest predictive power and most significant and dominant influence compared to all other independent variables. This finding affirms the crucial role of education as a vital barrier against early marriage and provides a strong foundation for policy intervention. Keywords: Early Marriage, Socioeconomic, Adolescent Girls